Study on In Vitro Growth of Rubus fraxinifolius Mutant (m1) Resulted from Gamma-Ray Irradiation (60Co) - Ismaini, Lily; Normasiwi, Suluh; Surya, Muhammad Imam; Destri, Destri (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2018)
Rubus fraxinifolius belonging to the wild raspberry group has not been developed in Indonesia. Mutation breeding using gamma-ray as mutagen which was combined with in vitro culture is one of acceleration effort to obtain superior characteristics of the fruit crops, such as larger fruit size, higher nutrition content, plant with less of spines and fruit storage ability. The R. fraxinifolius seeds were irradiated with different doses of gamma-ray ranging from 0 to 500 Gy using the 60Co (Cobalt). This research aimed to determine in vitro growth of R. fraxinifolius mutant (M1) after irradiation using gamma-ray. The results showed that the highest percentage of seed germination was obtained on the doses of 100 and 200 Gy. Furthermore, the subculture of R. fraxinifolius mutant (M1) on MS medium with the addition of BA showed the different growth on number of shoots, number of leaves, and plantlet height. Moreover, R. fraxinifolius control showed higher value of shoots, number of leaves, and plantlet height at 4 and 8 weeks after subculture compared to R. fraxinifolius mutant. MS medium with the addition of IBA showed that the number of roots of R. fraxinifolius control (5.75) was higher than that of R. fraxinifolius mutant (M1) (4.83).